2007
DOI: 10.3928/01484834-20070601-08
|View full text |Cite
|
Sign up to set email alerts
|

Native American High School Students' Perceptions of Nursing

Abstract: <h4>ABSTRACT</h4> <P>A pilot study was conducted to determine changes in Native American high school students’ knowledge and opinions about nursing after attending a 6-day residential summer nursing institute. To date, Native American high school students, particularly those interested in nursing, have not been well researched. Seventeen high school students affiliated with nine Northwest tribes participated in this study. A 66-item, investigator-constructed, pretest-posttest survey included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…Of the 10 studies, only Hoke (2006) identified and devoted a section of the paper to explaining the application of two theories: the Self-Concept Theory and the Theory of Planned Behavior. Although Katz (2007) discussed the importance of a culturally appropriate model to guide the assessment, implementation, and evaluation of an educational program for a specific population of Native Americans and Alaska Natives, the model was not used in the conduct of the study. The remaining eight studies failed to mention or refer to a theoretical framework.…”
Section: Brief Overview Of Research Processesmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 10 studies, only Hoke (2006) identified and devoted a section of the paper to explaining the application of two theories: the Self-Concept Theory and the Theory of Planned Behavior. Although Katz (2007) discussed the importance of a culturally appropriate model to guide the assessment, implementation, and evaluation of an educational program for a specific population of Native Americans and Alaska Natives, the model was not used in the conduct of the study. The remaining eight studies failed to mention or refer to a theoretical framework.…”
Section: Brief Overview Of Research Processesmentioning
confidence: 99%
“…Examination of the demographic characteristics of samples, across the studies reporting this information, revealed that the majority of study participants were White, school-aged, girls (Cohen et al, 2004;Drenkard et al, 2002;Grossman et al, 1989;Kohler & Edwards, 1990;May, Champion, & Austin, 1991;Palumbo et al, 2008;Tomey et al, 1996). Two studies deviated from this trend with samples that were primarily male (Hoke, 2006) or Native American (Katz, 2007). Participants were recruited from both rural (Cohen et al; Palumbo et al; Tomey et al) and urban settings (Hoke; Palumbo et al), as well as both public (Hoke; Kohler & Edwards) and private school systems (Grossman et al).…”
Section: Brief Overview Of Research Processesmentioning
confidence: 99%
See 3 more Smart Citations